1989
DOI: 10.1007/bf02602928
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of chromosome bands: Molecular ecology of noncoding DNA

Abstract: Giemsa dark bands, G-bands, are a derived chromatin character that evolved along the chromosomes of early chordates. They are facultative heterochromatin reflecting acquisition of a late replication mechanism to repress tissue-specific genes. Subsequently, R-bands, the primitive chromatin state, became directionally GC rich as evidenced by Q-banding of mammalian and avian chromosomes. Contrary to predictions from the neutral mutation theory, noncoding DNA is positionally constrained along the banding pattern w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
112
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(119 citation statements)
references
References 129 publications
6
112
1
Order By: Relevance
“…This conclusion is incompatible with previous observations using chromosome banding studies (Holmquist 1989) and density gradient centrifugation (Thiery et al 1976;Hughes et al 2002), which reported the lower level of GC heterogeneity in the turtle genome. Apart from the problems in sensitivity of the above indirect methods, the effect of lineage-specific events such as expansion of repetitive elements with extreme GC-contents might reconcile this difference.…”
Section: Insight Into the Evolutionary History Of Intra-genome Gc Hetcontrasting
confidence: 99%
See 1 more Smart Citation
“…This conclusion is incompatible with previous observations using chromosome banding studies (Holmquist 1989) and density gradient centrifugation (Thiery et al 1976;Hughes et al 2002), which reported the lower level of GC heterogeneity in the turtle genome. Apart from the problems in sensitivity of the above indirect methods, the effect of lineage-specific events such as expansion of repetitive elements with extreme GC-contents might reconcile this difference.…”
Section: Insight Into the Evolutionary History Of Intra-genome Gc Hetcontrasting
confidence: 99%
“…The existence of intra-genomic GC heterogeneity in reptiles has not been fully confirmed by chromosome banding studies (Holmquist 1989) and density gradient centrifugation (Thiery et al 1976;Hughes et al 2002). However, some recent studies at the nucleotide level suggest that GC heterogeneity exists in reptilian genomes, based on variations in GC-contents in exonic third positions (GC 3 ) and introns of a limited number of genes (Hughes et al 1999;Belle et al 2002;Hamada et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…1e). This may support the recent findings that R-bands contain more conserved DNA sequences than G-bands (for reviews, see Holmquist, 1989; Bickmore and Sumner, 1989). These data further confirm Ohno's hypothesis that the X chromosome has been highly conserved during mammalian evolution (Ohno, 1973).…”
Section: Resul Ts and Discussionsupporting
confidence: 85%
“…S6. somes are (G+C)-rich, CpG-rich and gene-rich [102][103][104] , exhibit features that are correlated with transcriptionally active DNA [105][106][107][108][109][110] , and have structural counterparts in the (G+C)-rich mammalian chromosomal R-bands (Table 8). Our current analysis shows that the different size classes of chicken chromosomes exhibit a number of correlated attributes.…”
Section: Exploring Chicken Genome Architecturementioning
confidence: 99%